DEVOLUSI RITUAL KEAGAMAAN DALAM KONSUMSI KONTEN KONTEMPLATIF DI MEDIA SOSIAL - Mulia Hasnah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation has shifted the private realm of religious rituals into the public sphere of social media, leading to a shift in spiritual values. This study analyzes the phenomenon of the devolution of religious rituals specifically, the decline in the depth of meaning and the shift in the value of sacredness resulting from the commodification of contemplative content on social media. The objective of this study is to identify the mechanisms by which social media algorithms reconstruct users’ spiritual experiences and to map the socio-religious implications of consuming short-form contemplative content. This study employs a qualitative approach using a critical-phenomenological methodology. Primary data were collected through in-depth interviews with 15 enthusiasts of digital spiritual content, as well as digital ethnographic (netnographic) observations on three major platforms (TikTok, Instagram, and YouTube Shorts). The data were analyzed using the theories of the “society of the spectacle” and the commodification of religion. The results indicate that social media algorithms trigger a shift in the meaning of spirituality from a profound transcendental experience to mere aesthetic visual consumption oriented toward instant gratification. Religious rituals are experiencing a decline in value, as the process of independent contemplation is being replaced by the performativity of digital piety. The implications of these findings point to the emergence of a new form of shallow spirituality, in which the interpretation of religion is heavily dependent on social media trends and engagement. This study makes a theoretical contribution by redefining the boundaries of the sacred in the era of digital religion.Ritual Devolution, Contemplative Content, Digital Religion, Netnography, Performativity of Piety.